Experimental and finite element investigations on the collapse of a Mero space truss roof structure – A case study - Caglayan, O.; Yuksel, E. (Elsevier BV, 2008)
Abstract A Mero space truss which is subject of this paper covering the roof of a reinforced concrete building was totally collapsed without any indication on February 25, 2003 at eastern part of Turkey. The plan dimensions of the space truss were 40 m by 25 m. The possible reasons of collapse of the roof system are inspected in this paper. During the observation on the site, several pipe elements and connection parts (Mero nodes and bolts) were gathered and then visual inspections and experimental studies were conducted on those parts. The meteorological records and observations of local persons were combined together to estimate the intensity of snow load in the region and it is compared with the code specified values. A mathematical model was prepared to evaluate the vertical load carrying capacity of the roof structure. The experimental and theoretical works conducted in this study indicate that the possible reasons of the collapse are underestimating of snow load intensity and some mistakes made in the elastic design of the truss.